Steels : microstructure and properties - Bhadeshia, H. K. D. H. (Harshad Kumar Dharamshi Hansraj), 1953-; Honeycombe, R. W. K. (Robert William Kerr) (Amsterdam ; Boston : Elsevier, Butterworth-Heinemann, 2006)
The most comprehensive and up-to-date textbook on the microstructure and properties of steels.
Iron and its interstitial solid solutions * The strengthening of iron and its alloys * The iron-carbon equilibrium diagram and plain carbon steels * The effects of alloying elements in iron-carbon alloys * Formation of martensite * The bainite reaction * Acicular ferrite * The heat treatment of steels -- hardenability * The tempering of martensite * Commercial Steels: New material to include Nanostructured Steels, Steels for the Energy and Automobile Industries * The embrittlement and fracture of steels * Stainless steel * Weld microstructures * Modelling of microstructure and properties *.
Previous edition: London : Edward Arnold, 1995. Primary author, Honeycombe.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Steel; Steel -- Metallurgy; Steel -- Metallography; Acier; Acier -- Métallurgie.; Acier -- Métallographie.; stalk (plant material); stems (object components); steels (firearm components); helves; honing steels; TECHNOLOGY & ENGINEERING -- Metallurgy; Steel; Steel -- Metallography; Steel -- Metallurgy; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.